Private school choice among Muslim parents: the public–private school decision in Delhi, India. (3rd August 2022) - Mousumi, Manjuma Akhtar; Kusakabe, Tatsuya
Abstract : This article examines Muslim parents' private school choice, their understanding of public–private schooling and how they navigate the choice between fee-free public schools and fee-charging private schools. This article draws on qualitative data from open-ended, semi-structured interviews with 38 parents from Muslim-majority areas in Delhi, India. The findings show that parents choose private schools for several reasons, such as their proximity, discipline, emphasis on Islamic teachings and values, safety and caring teachers. The analysis suggests that structural and social factors influence and construct parents' choice of a particular school. The neighbourhood where they reside, their minority status, their socio-economic and demographic profile, and the type of schools that are available to them influence their decision making.